Matching Boundary Conditions for the Euler–Bernoulli Beam - Yaoqi Feng; Xianming Wang (Shock and Vibration)
Artificial boundary conditions play a crucial role in the dynamic simulation of infinite Euler–Bernoulli beams. In this paper, a class of artificial boundary conditions, matching boundary conditions (MBCs), is presented to provide effective absorption of incident waves in numerical simulations of the Euler–Bernoulli beam. First, matching boundary conditions are proposed based on the space central difference scheme of the Euler–Bernoulli beam, and then, the specific coefficients of MBCs are determined by matching the dispersion relation. Moreover, reflection coefficient study and numerical tests are carried out to analyze the effectiveness of the proposed MBCs, indicating a remarkable agreement. Taken together, the proposed boundary conditions herein can absorb dispersive waves efficiently and are more compact than previous artificial boundary conditions, particularly suitable for real-time simulation.